Reducing smallholder farmers’ risk through agricultural advisories and climate smart agriculture in Northern Ghana - Kizito, Fred; Mponela, Powell; Girvetz, Evan Hartunian (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
AICCRA baseline data was collected from target populations that were previously engaged in CCAFS and counterfactual communities from 6 regions of Ghana and 4 ecological zones namely: Transition, Coastal Savannah, Guinea Savannah, and Sudan Savannah (MAP). The counterfactual communities from 6 regions of Ghana included Greater Accra, Central, Upper East, Upper West, Bono East, and Northern Regions. Both Climate Information Services (CIS) and Climate Smart Agriculture (CSA) demands vary across different ecoregions with respect to variations in climatic suitability/limitations, farming systems, cultural norms, and livelihood strategies. The socio-ecological differences have strong bearing on men’s and women’s mitigation and adaptive responses.